Structure and Properties of Materials - Tuxtayev Jamshed Jurayevich (Genius Journals, 2022)
This article provides a definition and classification of metals. Elementary crystal lattices. Characteristic features of ferrous metals. Atomic-crystalline structure of metals. Scheme of arrangement of elementary geometric cells in atomic lattices of metals and alloys. Geometric forms of elementary crystal cells.
Keywords: Metal; mechanism; chemical; physics; engineering; element